Decentralization of Public Authorities in Ukraine: Administrative-legal, Environmental, Social and Customs Aspects - Oleksandr Hladii; Oleksandr Bondarchuk; Yevgeny Zhadan; Ihor Kucher; Vadym Samus (UIN Sunan Gunung Djati, 2023)
The purpose of the research is to reveal the administrative-legal, environmental, social and customs principles of decentralization of public authority in Ukraine. Main content. The article reveals the main definitions of decentralization of power, analyzes advantages and disadvantages of the decentralization process in the public administration system. The article also presents the basic typology of decentralization of power in foreign countries and characterizes these types, as well as an attempt to summarize the reasons for performing decentralization in Ukraine. Â Methodology:Â The use of systemic, functional, and structural methods in this study made it possible to define concepts, types, as well as to establish the reasons for introduction of the decentralization reform in Ukraine. Conclusions. Various approaches to performing the reform in European countries and its results have been considered, which is due to the need to implement decentralization in Ukraine. The result of the work consists in determination of the main definitions of the decentralization of power, analysis of advantages and disadvantages of the decentralization process, definition of the main types of decentralization, as well as generalization of the main reasons for introduction of decentralization in Ukraine.